Replacement of table sugar with clarified rice syrup in beverages - Masood, S; Ashraf, M; Ahmad, I; Nisa, Alim un (Bangladesh Journal of Scientific and Industrial Research, 2022)
The worst element in the modern diet is white sugar, which contains the toxic fructose. As a result, many people have started avoiding fructose and switching to fructose-free sweets. Rice Syrup, for example, contains no fructose. White sugar was replaced with clarified rice syrup in this study. At a pilot plant scale, products such as red herbal syrup, chocolate syrup, cardamom syrup, aloe vera syrup, and plum syrup were made utilizing rice syrup in place of white sugar. During the shelf-life study, all parameters, including microbiological, physicochemical and sensory properties, were found acceptable. In addition, at zero weeks and 48 weeks, the effect of storage days on pH, acidity, brix, sugars content, and sensory attribute was determined. During storage, no notable changes in quality metrics were found. Bangladesh J. Sci. Ind. Res. 57(1), 23-26, 2022